Integrated personality profiling for academic performance - Yunus, Ahmad Rozelan; Syed Hassan, Syed Najmuddin; Kamarudin, Mohd Fauzi; Abdul Majid, Izaidin; Mohd Saufi, Nor Salahfiah (2018)
The importance of personality profiling can be observed especially in education and human resource management. Thus lack of ability to provide holistic and integrated personality domains of individual personality needed in dynamic academic challenge and fast changing organization. This project aims to develop a holistic and integrated personality framework for profiling tools utilizing and adapting established personality instruments. The main focus user of this profiling tools are students, academics personnel and organization administration personnel. The personality instruments developed based on literature related to the Psychometric Profiling Model widely used. The developed framework, was used as the core concept of integrated and automated profiling tools system. The system will be computer based and it will named as i-PRO (Integrated Personality Profiling System). Subsequently the focus of this initial study is to a group of 380 students applying random sampling method. The study was to provide evidence of relationship between P-E fit and environment area of specialization based on Holland’s Individual-Environmental Congruence Theory. One domain of i-PRO used was individual-environment fit and career interest domain. The main finding showed no significant differences in academic achievement between congruent students compared to non-congruent students. Results also showed that students from five out of seventeen academic programs are congruent with the academic program classification proposed by Holland in The Educational Opportunities Finder. Based on the research findings, several implications and recommendations were put forward.